Electro-optical properties of poly(N-vinyl carbazole) nanoclay composites - Ozerol, Esma Ahlatcioglu (SPRINGER, 2019)
In this work, different weight percentages of nanoclay (NC) (2% and 5%) and N-vinyl carbazole were prepared by chemical polymerization. For investigation of structure, optical and morphologies of samples, Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy and scanning electron microscopy were used, respectively. Moreover, dielectric properties of composites were examined using dielectric analysis system and vector network analyzer system at high frequency. It was seen that the values of the real and imaginary dielectric constants and loss factor decrease with doping nanoclay into poly(N-vinyl carbazole) (PNVC). The conductivity properties of all samples were studied, and s parameter was calculated. Up to 1.7 GHz, s parameter value correlated with Jonscher power law, and between 1.7 GHz and 20 GHz, s parameter value correlated with superlinear power law. Also, the atomic polarization behaviors in the high-frequency regions have been obtained for PNVC and PNVC doped with 2%, 5% NCs at 25 degrees C.
Keywords: Poly(N-vinyl carbazole); Nanoclay; Composite; Conducting polymer; Dielectric; SILICON NANOCRYSTALS; GRAPHENE; CONDUCTIVITY; POLYMERS; SENSORS; BLENDS; LIQUID; Polymer Science